The craft of research - Booth, Wayne C. 4 0 16; Colomb, Gregory G.,;Williams, Joseph M.; 5 (Chicago : University of Chicago Press, 1995)
Presents research skills that may be used in all fields of study, including how to choose a topic, generate research questions, find sources for gathering evidence, argue effectively, and write and revise a paper.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Methodology. -- Research;Technical writing. -- 20; 20; 2